Genetic Characteristics and Range of Antibacterial Activity of the Bacteriophages, which are a Part of Manufactured Serie of Drugs - Pyobacteriophage Polyvalent Purified - N. V. Tikunova; N. N. Voroshilov; O. A. Polygach; V. V. Morozova; A. Y. Tikunov; A. M. Smokers; V. V. Vlasov (Эпидемиология и вакцинопрофилактика, 2016)
Pyobacteriophage polyvalent cleared (preparation) is active against 85.0 - 99.6% clinical strains of bacteria Proteus spp., Streptococcus spp., Klebsiella pneumoniae, Escherichia coli, Staphylococcus spp., and Pseudomonas aeruginosa. The preparation surpasses the majority of antibiotics in the width of a range of antibacterial activity and is comparable only with modern antibiotics of the last generations. Unlike the majority of antibiotics, the preparation doesn't cause toxic and allergic reactions, has no contraindications to application, including age, is allowed for use for newborns and children of early age that gives the chance to regard him as highly effective and safe medicine for antibacterial therapy. The results of metagenomic analysis of pyobacteriophage polyvalent cleared indicate that the product contains only lytic bacteriophages and does not contain lysogenic bacteriophages, that guarantees high concentration of lytic bacteriophages in a preparation high degree of his antibacterial and clinical efficiency and genetic safety of its clinical application.